Penerapan Game-Based Learning Berbantuan Kahoot Dalam Pembelajaran Teks Negosiasi Pada Peserta Didik Kelas X SMK Bina Warga Bandung - Windy Aida Adam; Titin Nurhayatin; Lili Sadeli (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2024)
This research is motivated by the low ability of students in analyzing negotiating texts that focus on content, structure, and language feature. This is due to the lack of variation of educators in choosing teaching methods and media. Selection of varied teaching methods and media can increase motivation and interest in learning. The purpose of this study was to examine the effectiveness and abilities of students in applying Kahoot-assisted game-based learning in learning to analyze negotiating texts and examine differences in ability between the experimental class and the control class which applied the discussion method. The research method used is a quantitative method with a quasi-experimental. The form of the research design is the pretest-posttest control group design. The data obtained are the pretest and posttest results from the experimental and control classes. The results of this study prove; 1) Kahoot-assisted game-based learning is effectively used in learning to analyze the content, structure, and language feature of negotiating text, as evidenced by the results of the Mann-Whitney test showing asymp. sig. 0.000; 2) students are able to analyze negotiating text, as evidenced by an increase in the average pretest score 75 to posttest 91.25; 3) and there are differences in the ability of students in the experimental class and the control class, it can be proven by the results of the Wilcoxon test showing asymp. sig. in both classes is 0.000. Thus, kahoot-assisted game-based learning can be used as a choice of teaching methods and media.